Making themselves at home: Strategies of self-representation in pioneer women's autobiographies - Thomas, Christa Maria Zeller (University of Ottawa (Canada), 2009)
This dissertation explores narrative strategies of self-identity in autobiographies by six pioneering women writers, each of whom lost what has traditionally been woman's place: her home. The accounts of emigration, expatriation, and exile by Anna Brownwell Jameson, Catharine Parr Traill, Susanna Moodie, Ada Cambridge, Isak Dinesen, and Alyse Simpson illustrate the implications of this loss, as each woman struggled to recover a sense both of home and of grounded identity. The writings span more than a hundred years, from the 1830s to the 1950s, and tell of lives lived in locations as different as Canada, Australia, and British East Africa (now Kenya), places that variously proved to be confining and/or liberating. By narrating the ways in which identity adapts to and is transformed by a new environment, these texts provide access to the construction and alteration of the self in relation to place. This study probes this process by using the concept of place, rather than the more conventional one of time, as the dominant category of analysis. My readings are both intertextual and interdisciplinary: they rely on theorizing by sociologists and psychologists concerned with the relationship between place and identity, studies on the same subject by literary scholars, and formulations by women's autobiography theorists. My investigation reveals, among other discoveries, that the gender-specific aspects of the process of adaptation persistently centre on the notion of homecoming and that they are articulated with reference to the figure of the mother.
Keywords: Literature, Modern.; Women's Studies.; Literature, English.